Uncertainty and the Federal Reserve's balance sheet monetary policy - Valentina Colombo; Alessia Paccagnini (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2024)
This study assesses the impact of financial uncertainty shocks in the US and explores the influence of monetary policy. Using a nonlinear Vector Autoregressive model, incorporating short-term interest rates and the Federal Reserve's balance sheet policy, we find that the reaction of the monetary policy is asymmetric across the business cycle. The state-dependent responses in consumption and investment significantly influence GDP fluctuations. A counterfactual analysis reveals that balance sheet-related monetary policy helps reduce both the duration and severity of the recessionary impacts caused by these shocks.
Keywords: C50; E32; E52; 330; Uncertainty; Smooth Transition VAR; Nonlinearities; Monetary Policy